2011
DOI: 10.1089/jop.2010.0188
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Sustained Release Nanoparticles Containing Stereoisomeric Dipeptide Prodrugs of Acyclovir

Abstract: Purpose: The objective of this study was to develop and characterize polymeric nanoparticles of appropriate stereoisomeric dipeptide prodrugs of acyclovir (L-valine-L-valine-ACV, L-valine-D-valine-ACV, D-valine-Lvaline-ACV, and D-valine-D-valine-ACV) for the treatment of ocular herpes keratitis. Methods: Stereoisomeric dipeptide prodrugs of acyclovir (ACV) were screened for bioreversion in various ocular tissues, cell proliferation, and uptake across the rabbit primary corneal epithelial cell line. Docking stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…exhibited different affinities to the peptide transporter, permeabilities and bioreversion rates in Caco-2 and rPCEC cell lines, as well as intestine, liver and ocular tissues (Talluri et al, 2008;Jwala et al, 2011). It was revealed that incorporation of one D-Val in a dipeptide diminished, but does not negate its affinity towards peptide transporters but significantly improve enzymatic stability of stereoisomeric dipeptide prodrugs to a large extent depending on the position of D-amino acid in a dipeptide conjugate (Tamura et al, 1996;Friedrichsen et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…exhibited different affinities to the peptide transporter, permeabilities and bioreversion rates in Caco-2 and rPCEC cell lines, as well as intestine, liver and ocular tissues (Talluri et al, 2008;Jwala et al, 2011). It was revealed that incorporation of one D-Val in a dipeptide diminished, but does not negate its affinity towards peptide transporters but significantly improve enzymatic stability of stereoisomeric dipeptide prodrugs to a large extent depending on the position of D-amino acid in a dipeptide conjugate (Tamura et al, 1996;Friedrichsen et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The peptidases and esterases are stereospecific and have high affinity for L-isomers. Therefore, incorporation of D-isomer in the prodrug can improve enzymatic stability of the prodrug in tissue (Talluri et al, 2009;Jwala et al, 2011). It was reported that L-valine in the terminal position increases the affinity of prodrugs to the peptide transporter protein in rabbit primary corneal epithelial cells (rPCEC) (Jwala et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Cytotoxicity of SN-38-SBEβCD complex on ovarian cancer cell lines A2780 and 2008 was evaluated by MTT assay (27)(28)(29) and compared with the cytotoxicity of SN-38 and irinotecan. As SN-38 is not soluble in water, a stock solution was made in DMSO and suitable dilutions were made in growth medium, keeping the final DMSO concentration less than 0.1%.…”
Section: In Vitro Cytotoxicity Studiesmentioning
confidence: 99%
“…These influx transporters have been demonstrated to be highly expressed on the apical surface of the corneal epithelium (21)(22)(23). This transporter has previously been targeted with amino acid and dipeptide prodrugs to improve corneal transport of poorly permeable drugs (23)(24)(25)(26)(27)(28)(29). Amino acids employed to generate amino acid and dipeptide prodrugs are of L-configuration as L-isomers possess high affinity and specificity towards peptide transporters (30,31).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, L-valine-D-valine-acyclovir (LDACV), D-valine-L-valine acyclovir (DLACV), and D-valine-D-valine-acyclovir (DDACV) displayed significant enzymatic stability in corneal cell and ocular tissue homogenates (24). The main objective of the present study is to investigate enhanced corneal absorption of stereoisomeric prodrug approach by improving aqueous solubility, corneal permeability, and circumvention of Pgp-mediated cellular efflux of prednisolone.…”
Section: Introductionmentioning
confidence: 99%